An evaluation of ring-based algorithms for the Eventually Perfect failure detector class - Wieland, J.; Larrea, M.; Lafuente, A. (15th EUROMICRO International Conference on Parallel, Distributed and Network-Based Processing (PDP'07), 2007)
This paper presents an evaluation of two families of ring-based algorithms implementing the eventually perfect failure detector class (diamPscr). The evaluation is based on two kinds of performance parameters: communication efficiency, which refers to the number of links that carry messages forever, and quality of service, which includes the capability of the failure detector for providing right answers as well as reaction and initial stabilization times. The first family of algorithms includes several communication-efficient implementations of diamPscr introduced in a previous work. For the second family, introduced in this work, we start from the design of a non communication-efficient diamQscr algorithm, and then we apply a transformation to obtain a diamPscr algorithm, including some optimizations to improve the quality of service